THE INFLUENCE OF PACKAGING AND PROMOTION ON THE PURCHASE DECISION OF TEMPE CHIPS IN SUNGAI LANGKAI SUB-DISTRICT, BATAM - Winda Evyanto; Asron Saputra; Triana Ananda Rustam; Yvonne Wangdra (JIM UPB (Jurnal Ilmiah Manajemen Universitas Putera Batam), 2023)
This study aims to describe the results of research on the Effects of Packaging and Promotion on the Purchase Decision of Tempe Chips from Home Industry in Sungai Langkai , Sagulung District, Batam. in addition to the importance of improving quality in terms of content, it needs special attention from various parties, both from the government and the private sector. , as well as universities as many universities have done through community service activities. This research focuses on looking at the implementation of packaging and promotion strategies. The research method used is quantitative research, the data source is 100 consumers of tempeh chips in Sungai Langkai , Sagulung District, Batam City. Data collection by observation, interviews and documentation, and data analysis by domain data analysis. The results of the discussion show that the labeling and packaging of the decision to buy tempeh chips in the Sungai Langkai sub-district, Sagulung sub-district, can be carried out well even though they are still traditional, but from time to time have changed for the better